2022
DOI: 10.1186/s12909-022-03769-x
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal imaging authority, levels of training, attitude, competence, and utilisation among clinical physiotherapists in Nigeria: a cross-sectional survey

Abstract: Background Direct-access physiotherapy practice has led to a global review of the use of differential-diagnostic modalities such as musculoskeletal imaging (MI) in physiotherapy. Objective To explore the MI authority, levels of training, attitude, utilisation, and competence among clinical physiotherapists in Nigeria. Methods This national cross-sectional study analysed a voluntary response sample of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…Thirdly, although rigorous pilot testing was conducted for our questionnaire, formal reliability and validity assessments could have been undertaken to increase and ensure the overall quality of our work. Moreover, studies from Ghana (Amuasi et al 2022) and Nigeria (Onyeso et al 2022) had reported 16% and 19% rate of online survey participation from healthworkers and physiotherapists, respectively, while in our study we reached nearly 10% of the targeted population. Because of the limited sample of respondents in some countries, our results could not be fully generalised to all French-speaking countries of sub-Saharan Africa.…”
Section: Limitations Of Our Studycontrasting
confidence: 54%
“…Thirdly, although rigorous pilot testing was conducted for our questionnaire, formal reliability and validity assessments could have been undertaken to increase and ensure the overall quality of our work. Moreover, studies from Ghana (Amuasi et al 2022) and Nigeria (Onyeso et al 2022) had reported 16% and 19% rate of online survey participation from healthworkers and physiotherapists, respectively, while in our study we reached nearly 10% of the targeted population. Because of the limited sample of respondents in some countries, our results could not be fully generalised to all French-speaking countries of sub-Saharan Africa.…”
Section: Limitations Of Our Studycontrasting
confidence: 54%
“…Twenty articles used quantitative methodologies, such as cohort, cross‐sectional, and randomized or non‐randomized, controlled designs (Addley et al., 2010; Bishop et al., 2017; Bornhöft et al., 2019; Childs et al., 2005; Domholdt & Durchholz, 1992; Donato et al., 2004; Durant et al., 1989; Gagnon et al., 2021; Gorman et al., 2010; Holdsworth et al., 2007; Jette et al., 2006; Keller et al., 2022; Kilner & Sheppard, 2010; Ludvigsson & Enthoven, 2012; Mitchell & de Lissovoy, 1997; Nordeman et al., 2006; Onyeso et al., 2022; Overman et al., 1988a; Richardson, 2005; Taylor et al., 2011); 9 used qualitative methodologies based on interviews, focus groups, or Delphi methods (Alshareef et al., 2023; Boakye et al., 2016; Burley et al., 2020; Chance‐Larsen et al., 2019; French & Galvin, 2017; Kumar & Grimmer, 2005; Lefmann & Sheppard, 2014; McMahon et al., 2016; Vader et al., 2022); 2 used a mixed methodology (Alkhouri et al., 2020; Fisher, 2020); seven involved knowledge syntheses such as systematic, scoping, critical, and narrative reviews (Boakye et al., 2016; Ferreira et al., 2019; Foster et al., 2012; C. Harris et al., 2020; Lackenbauer et al., 2017; Lin et al., 2020; Ojha et al., 2014); 9 were viewpoints (editorials and clinical commentaries) (Bishop et al., 2013; W. G. Boissonnault et al., 2010; W. G. Boissonnault & Ross, 2012; W. Boissonnault & Goodman, 2006; Crane & Delany, 2013; Fleming‐McDonnell et al., 2010; Juneja et al., 2020; Lebec & Jogodka, 2009; McMahon et al., 2016); and 18 were from grey literature, including international references, books, and theses (APTA, 2012, 2...…”
Section: Resultsmentioning
confidence: 99%
“…The procedure was adopted from a previous national online survey among Nigerian physiotherapists [ 23 ]. An online, web-based questionnaire was prepared using google form and made accessible using a web link.…”
Section: Methodsmentioning
confidence: 99%